2016
DOI: 10.3233/jad-160328
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide and Risk of Future Cognitive Impairment in the REGARDS Cohort

Abstract: 1 Background: Improved understanding of the etiology of cognitive impairment is needed to develop effective preventive interventions. Higher amino-terminal pro-B-type natriuretic peptide (NT-proBNP) is a biomarker of cardiac dysfunction associated with risk cardiovascular diseases and stroke in apparently healthy people.Objective: To study the association of NT-proBNP with risk of incident cognitive impairment.Methods: The Reasons for Geographic and Racial Differences in Stroke is a national cohort study of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Finally, we found that NT-proBNP levels were associated with lower DSST scores. This finding supports recent observations of a longitudinal association between NT-proBNP and future cognitive impairment ( 39 , 40 ). In fact, one study observed a longitudinal association with processing speed measured by DSST but not other domains ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we found that NT-proBNP levels were associated with lower DSST scores. This finding supports recent observations of a longitudinal association between NT-proBNP and future cognitive impairment ( 39 , 40 ). In fact, one study observed a longitudinal association with processing speed measured by DSST but not other domains ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…Greater NT-proBNP concentration was associated with greater functional impairment, worse cognitive functioning and more severe depressive symptoms. Previous studies showed that elevated NT-proBNP concentrations predict worse cognitive functioning and greater risk of cognitive decline in the general population 32 , 33 . An association of higher NT-proBNP concentration with greater depressive symptom severity was previously documented in patients with coronary disease 34 and diabetes 35 .…”
Section: Discussionmentioning
confidence: 98%
“…It must be investigated if measures to reduce circulating galectin-3 levels can improve cognitive functions. Finally, whether a multibiomarker panel approach would increase the yield for early detection of cognitive impairment remains to be established [41] .
Research in Context Systematic review: The authors reviewed the relevant studies on association of galectin-3 with cognitive impairment and neurological disorders using PubMed and Google scholar by going through the references of the relevant articles which are cited in this article.
…”
Section: Discussionmentioning
confidence: 99%